Architectural self-fabrication. (18th December 2017) - Cascone, Paolo; Galdi, Flavio; Giglio, Andrea; Ciancio, Elena
Abstract: The paper will focus on the role of computational design and digital fabrication in the processes of urban and architectural self-regeneration of existing infrastructures and buildings. The Architectural Fabrication research agenda takes inspiration from some of the concepts mentioned in Christopher Alexander's essay 'Systems generating systems' (1968). It aims at introducing ways in which systems thinking and computer aided manufacturing can be most directly applied to the built environment. Hacking architectural spaces, by evolving their genetic spatial and structural codes, is developing the idea of optimizing resources involving inhabitants rather than generating other top down architectural solutions. During the last decades (starting from the book of Mario Carpo, 'The Digital Turn in Architecture') the digital shift in architectural design has generated a new discipline with the aim to define an innovative way to bridge the notion of nature with the one of teknè. From such a cultural milieu many research agenda were focusing on the concepts of morphogenesis and evolutionary thinking inspired by the work of French philosophers Gilles Deleuze and Felix Guattari based on the theory of complex systems. Despite this interest in bridging an evolutionary approach with the notion of emergent technologies in architecture (well described in the book 'The Architecture of Emergence' of Michael Weinstock) only a very few researchers have investigated on the potential of computational design as a driver for the ecological rehabilitation of existing infrastructures. As a matter of fact, the computational designers were so worried to claim for a new aesthetical identity of their discipline while a new opportunity was emerging for applying this evolutionary approach in order to hack existing structures. The idea of living infrastructures is related to the possibility of developing contextual algorithms in order to customize standard solutions with a post-human process that creates diversified spatial configurations out of very rigid organizational systems. Therefore, the paper will also talk about the Hacking Gomorra project as a possible paradigm of experimenting a 3D printing protocol for the environmental rehabilitation of a mega-structural housing building in Naples (Italy). Abstract : Flow chart of digital process Hacking Gomorra project – courtesy of COdesignLab.